New trends in dentistry: plant extracts against Enterococcus faecalis. The efficacy compared to chlorhexidine - Adriana Lígia de Castilho; Cintia Helena Coury Saraceni; Ingrit Elida Collantes Díaz; Mateus Luís Barradas Paciencia; Ivana Barbosa Suffredini (Sociedade Brasileira de Pesquisa Odontológica, 2013)
Enterococcus faecalis is an important pathogen associated with endodontic diseases, and its elimination and control are of paramount importance, as it represents one of the major causes of failure in the treatment of endodontic disease. Twenty-five plant extracts obtained from Brazilian forests were found to be effective against planktonic E. faecalis and were subjected to two traditional antibacterial assays, the microdilution broth assay (MDBA) and the disk diffusion assay (DDA), using chlorhexidine (CHX) as a control. Seven out of 25 extracts showed significant antibacterial activity and were tested in a biofilm assay, and three of these extracts were subjected to chemical fractionation. Residues were tested for their antibacterial activity, and the first chemical findings were described based on thin layer chromatography (TLC). Extracts obtained from Ipomoea alba, Symphonia globulifera and Moronobea coccinea showed significant bactericidal activity in the MDBA. The same I. alba and S. globulifera extracts, as well as the extract obtained from Connarus ruber var. ruber, showed significant activity in the DDA. RH2O obtained from Psidium densicomum and Stryphnodendron pulcherrimum showed better antibacterial activity compared to the respective crude extracts and CHX. TLC analysis showed that phenolic compounds and triterpenes represent the first findings of chemical groups that may occur in all species. The results of the present study include the discovery of six active extracts against planktonic E. faecalis and support further testing via assays involving biofilm formation, as well as the determination of the compounds' chemical profiles, as their activity was significantly better than that observed for CHX.